2009
DOI: 10.3959/2008-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Radial Growth Relationships of Northern Latitudinal Range Margin Longleaf Pine (Pinus palustrisP. Mill.) in the Atlantic Coastal Plain of Southeastern Virginia

Abstract: Climate and longleaf pine (Pinus palustris P. Mill.) radial growth relationships have been documented within its southern and western distribution. However, knowledge of this relationship is lacking along its northern latitudinal range margin (NLRM). Based on the principles of ecological amplitude, limiting factors, and studies of coniferous species in eastern temperate forests of the U.S., we hypothesized that the radial growth of longleaf pine in mixed pine-hardwood forests is responding to winter temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…Growth is influenced by non-climatic and climatic factors , and most NE US trees are moisture-rather than temperature-sensitive (Stahle and Hehr, 1984;Cook, 1991;Meko et al, 1993). Conifers at high elevations or northern range margins have the strongest significant and positive relationships to temperature (Conkey, 1982;Pederson et al, 2004;Bhuta et al, 2009), and the temperature sensitivity of red spruce wood density (Conkey, 1986) and Atlantic whitecedar ring widths (Hopton and Pederson, 2005) in particular have produced reliable reconstructions. Red spruce sensitivity to acid rain, however, may complicate the most recent temperature reconstructions (Webster et al, 2004).…”
Section: Tree-ring Recordsmentioning
confidence: 99%
“…Growth is influenced by non-climatic and climatic factors , and most NE US trees are moisture-rather than temperature-sensitive (Stahle and Hehr, 1984;Cook, 1991;Meko et al, 1993). Conifers at high elevations or northern range margins have the strongest significant and positive relationships to temperature (Conkey, 1982;Pederson et al, 2004;Bhuta et al, 2009), and the temperature sensitivity of red spruce wood density (Conkey, 1986) and Atlantic whitecedar ring widths (Hopton and Pederson, 2005) in particular have produced reliable reconstructions. Red spruce sensitivity to acid rain, however, may complicate the most recent temperature reconstructions (Webster et al, 2004).…”
Section: Tree-ring Recordsmentioning
confidence: 99%
“…Growth of NC trees was also positively correlated to average February and April temperatures, and temperature has been shown to influence cambial reactivation and earlywood tracheid production (Dufour and Morin, 2013) in variety of tree species including loblolly pine in NC (Woods and Debrunner, 1970). Correlations between radial growth and February temperature have been reported for southern pines at their northern latitudinal range margin (Kirwin et al, 2007;Bhuta et al, 2009). Environmental conditions, in particular temperature (Begum et al, 2012), that increase photosynthesis before the resumption of growth are correlated with earlywood formation in temperate zones (Lebourgeois, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lodewick (1930) found no relationship between radial growth and temperature, whereas Coile (1936) identified a negative correlation between radial growth and August temperature. At the northern range for longleaf pine, Bhuta, Kennedy, and Pederson (2009) noted that southern Virginia sites responded positively to temperature, suggesting that winter temperatures are more influential at the species northern range limit. Henderson and Grissino-Mayer (2009) stated the importance of collecting data from multiple sites for tree-ring and climate research in that subtle differences in tree growth can occur due to both site heterogeneity and intraspecific variability in climate response (Grissino-Mayer and Butler 1993).…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…After cross-dating, samples were digitally scanned at 1,200 dpi (EPSON, Expression 10000XL), and both total ring width (TRW) and latewood ring width (LW) were measured to the 0.001 mm using the computer program WinDEN-DRO (WinDENDRO for Tree-ring Analysis, Regent Instruments Canada Inc., Qu ebec, QC, Canada). We selected these measurements as previous research has found they both correlate with precipitation, temperature, and drought (Lodewick 1930;Devall, Grender, and Koretz 1991;Meldahl et al 1999;Foster and Brooks 2001;Henderson and Grissino-Mayer 2009;Bhuta, Kennedy, and Pederson 2009).…”
Section: Processingmentioning
confidence: 98%